¿Avanza la iniciativa de ley presidencial hacia un Sistema de financiamiento político chileno más equitativo y transparente? - Dorfman, Ricardo Gonzalez (Ballot, 2015)
At the end of last year the presidency of the Republic of Chile sent it’s National Congress a draft law as part of a measure package with the purpose of strengthening the country’s democratic system, improving the regulation of electoral campaigns and the attributions of the control organ.This analysis aims at the diverse aspects of the presidential law draft, that intends to restructure in a unique way the political financing system and the its regimes.This article will point the pros and cons of the aspects of the proposed reform.